Monoterpene antifungal activities: evaluating geraniol, citronellal, and linalool on Candida biofilm, host inflammatory responses, and structure–activity relationships - Vasconcelos, Priscilla Guimarães Silva; Lee, Kyu Min; Abuna, Gabriel Flores; Costa, Edja Maria Melo Brito; Murata, Ramiro Mendonça (Frontiers in Pharmacology, 2024)
Introduction: Despite the rising concern with fungal resistance, a myriad of molecules has yet to be explored. Geraniol, linalool, and citronellal are monoterpenes with the same molecular formula (C10H18O), however, neither the effect of these compounds on inflammatory axis induced by Candida spp. nor the antibiofilm Structure-Activity Relationship (SAR) have been well-investigated. Herein we analyzed geraniol, linalool and citronellal antifungal activity, cytotoxicity, and distinctive antibiofilm SAR, also the influence of geraniol on Candida spp induced dysregulated inflammatory axis, and in vivo toxicity. Methods: Minimal inhibitory (MIC) and fungicidal (MFC) concentrations against Candida spp were defined, followed by antibiofilm activity (CFU–colony forming unit/mL/g of dry weight). Cytotoxic activity was assessed using human monocytes (THP-1) and oral squamous cell (TR146). Geraniol was selected for further analysis based on antifungal, antibiofilm and cytotoxic results. Geraniol was tested using a dual-chamber co-culture model with TR146 cells infected with C. albicans, and THP-1 cells, used to mimic oral epithelium upon fungal infection. Expression of Candida enzymes (phospholipase–PLB and aspartyl proteases–SAP) and host inflammatory cytokines (interleukins: IL-1β, IL-6, IL-17, IL-18, IL-10, and Tumor necrosis factor–TNF) were analyzed. Lastly, geraniol in vivo toxicity was assessed using Galleria mellonella. Results: MIC values obtained were 1.25–5 mM/mL for geraniol, 25-100 mM/mL for linalool, and 100–200 mM/mL for citronellal. Geraniol 5 and 50 mM/mL reduced yeast viability during biofilm analysis, only 500 mM/mL of linalool was effective against a 72 h biofilm and no biofilm activity was seen for citronellal. LD50 for TR146 and THP-1 were, respectively: geraniol 5.883 and 8.027 mM/mL; linalool 1.432 and 1.709 mM/mL; and citronellal 0.3006 and 0.1825 mM/mL. Geraniol was able to downregulate expression of fungal enzymes and host pro-inflammatory cytokines IL-1β, IL-6, and IL-18. Finally, safety in vivo parameters were observed up to 20 mM/Kg. Discussion: Despite chemical similarities, geraniol presented better antifungal, antibiofilm activity, and lower cytotoxicity when compared to the other monoterpenes. It also showed low in vivo toxicity and capacity to downregulate the expression of fungal enzymes and host pro-inflammatory cytokines. Thus, it can be highlighted as a viable option for oral candidiasis treatment.